Beloved tracker system / Canigjia Song Twet @ Thwaites ... [et al.] - Twet @ Thwaites, Canigjia Song; Mohd Nasir, Ahmad Amir Muhsin; Roslan, Mohd Haikal Rizaki; Khirul Ashar, Nur Dalila; Hairuddin, Muhammad Asraf; Mohd Yusoff, Zakiah (Universiti Teknologi MARA, Kedah, 2019)
The children related issue due to kidnapping, missing and threatening have been major concerns among parents. Regular monitoring of their children seems very difficult for working parents while worrying about their children safe. Therefore, a beloved tracker system is innovated to secure the children and protect them from any case of emergency whenever the push button has been pressed. It consists of the latest Arduino board and embedded GSM with an attached GPS module with an OLED display. The objective of this works purposely to introduce a miniaturized device associated with children security and develop a notification system to inform the current positional location and enable of sending SMS towards parents whenever the child feels insecure. The novelty of this device as compared to the existing tracking device in the market are as following; miniaturized in size, wide coverage of communication as compared to Bluetooth communication and attractive. The proposed device is significant to assist in tracking the exact location of the user. The designed tracking system has full potential to be commercialized among children or even can be used by women or old people which concerns on their safety. In the future, several works have been planned to market the product nationwide.